Survival Strategy of Traditional Small Retail in Competition with Modern Large Retail - Andi Sri Wahyuni (Faculty of Economics, Universitas Sriwijaya, 2023)
This study aims to understand how traditional small retail businesses in Italy compete with large modern retailbusinesses. I conducted direct observation for 145 hours in three regions in Italy—Pescara, Chieti, and the factory area—and then conducted a thematic analysis of their survival strategy. I find that the main factor that determines the sustainability of tabaccai is the support of the local government, which is strengthened by the local society and the ability of the owners to adapt to the environment. These empirical findings provide a new recommendation for traditional small retail businesses in developed countries on how to survive amid the growth of large modern retail businesses.